Risk Management Analysis of Information Technology with Failure Mode and Effect Analysis Method at PT XYZ - Virgiawan, Adisty Kharisma; Santi, Rusmala; Alfresi, Aminullah Imal (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2025)
PT Kencana Inti Perkasa is a company engaged in the management of crude palm oil (Crude Palm Oil) which uses information technology for its smooth operations. In the company there are potential information technology risks that can have an impact on the company so that they need to be identified and given an assessment. Risk problems that occur in PT Kencana Inti Perkasa's information technology are damaged hardware, virus attacks, risks to data, and risks to the network. This research aims to produce RPN values, get a list of risk priorities and develop recommendations for control measures using the Failure Mode and Effect Analysis method. This process involves identifying failure modes, assessing the severity, frequency of occurrence, and detectability of each failure mode. The final result of this research found that there are 30 failure modes consisting of 4 risks categorized as High, 2 risks categorized as Medium, 22 risks categorized as Low, and 2 risks categorized as Very Low. The highest Risk Priority Number (RPN) value, 167.83 and in the High category, arises from the incorrect use of printers caused by human error, including technological resources that are routinely utilized by the company. Another risk in the High category is the slow network capacity with an RPN of 152.06. Furthermore, computer damage due to virus attacks obtained an RPN value of 122.26, while illegal access to PC information was also categorized as High with an RPN value of 121.09, which belongs to the company's vital technology resources. These findings indicate that these risks need to be the main focus in handling, considering the high RPN value indicates a significant level of urgency.